An Interdisciplinary Study of Taking Property by False Means - Miladisani Ammar Umah; Dewi Purnamasari (Green Philosophy: International Journal of Religious Education and Philosophy, 2025)
This article discusses the concept of acquiring wealth through wrongful means from an Islamic perspective through an interdisciplinary study approach. In Islam, wealth is viewed as a trust that must be acquired and utilized in accordance with sharia provisions, so that any form of acquisition carried out through unlawful means is viewed as an act that damages the public interest and violates religious provisions. This study uses a qualitative method with a literature study approach to analyze the forms of acquiring wealth through wrongful means, such as usury, gharar, risywah, tadlis, and maysir, and their impacts on various aspects of life. The analysis is conducted through the perspectives of Islamic law, economics, psychology, and socio-culture. The results of the study indicate that acquiring wealth through wrongful means not only harms individuals but also affects the social, economic, and moral stability of society. In addition, this practice is viewed as a form of deviation from the essential function of wealth in Islam, namely as a means to realize the common good. This study emphasizes the importance of implementing sharia values in economic and social practices as a preventive measure against injustice and injustice in society.